Slovenian – The Language of Instruction in Higher Education - Skubic, Darija; Baloh, Barbara (Slavia Centralis, 2026)
In the twenty-first century, an increasing number of individuals are bilingual or multilingual, while English remains the lingua franca in both European and non-European contexts. The present paper examines the attitudes of students of preschool education and classroom teaching at the Faculty of Education, University of Ljubljana, and the Faculty of Education, University of Primorska, towards Slovene being the language of instruction in higher education. Relevant literature was inspected and a survey questionnaire developed for the research. The latter contained 20 statements rated on a five-point Likert scale. It was completed by 154 students from the Faculties of Education in Ljubljana and Koper. Overall, the results show that students express a positive attitude towards Slovene as the language of instruction in higher education.
Keywords: preschool education; primary teacher education; Slovene; students; higher education